Development of CRISPR-Cas9-based genome editing tools for non-model microorganism Erwinia persicina - Tingfeng Cheng; Xinyan Cao; Yuchen Wang; Lei Zhao (Synthetic and Systems Biotechnology)
Erwinia persicina is a bacterium that has been known to produce secondary metabolites, such as andrimid, pink pigment, and exopolysaccharides, and to infect more than twenty plant species. However, traditional gene manipulation methods have been hindered by the inefficient of suicide plasmid-mediated genome editing. In this study, we describe the successful application of the CRISPR-Cas9 system in E. persicina. Efficient genome editing was achieved by substituting the native gRNA promoter with J23119 in a single-plasmid system (pRed_Cas9_ΔpoxB) and optimizing the gRNA design. The use of double gRNAs led to the deletion of a 42 kb genomic fragment, and the incorporation of a sacB screening marker facilitated iterative knockouts. Additionally, a 22 kb plasmid containing a self-resistance gene was conjugally transferred into E. persicina, resulting in the insertion of a 6.4 kb fragment with 100 % efficiency. Furthermore, we demonstrated the expression of shinorine, an anti-UV compound, within the E. persicina chassis. This study establishes E. persicina as a promising chassis for synthetic biology and provides a model for gene-editing systems in non-model microorganisms.